Implementasi Produk Pembiayaan Murabahah di Koperasi Syariah Berkah Kabupaten Bandung Barat - Bambang Wisnuadhi; Ine Mayasari; Dimas Sumitra Danisworo; Ghifari Munawar; Hasbi Assidiki Mauluddi; Lukmannul Hakim Firdaus; Wendi Wirasta (Jurusan Akuntansi Politeknik Negeri Bandung, 2022)
Sharia cooperatives are mediators for providers of funds and users of funds so that borrowed funds can be used optimally. In sharia cooperatives there is financing whose purpose is to meet the needs of its members. Murabaha financing is the most preferred financing by members, usually used to meet consumptive needs. The purpose of this study was to determine the implementation of murabahah contracts in murabahah financing products in the Berkah Syariah Cooperative, West Bandung Regency. This research is a qualitative research with a case study approach. The data used in this study is the primary data of the Berkah Syariah Cooperative and for data collection techniques will use three events, namely, observation, interviews and documentation. Based on observations and interviews that have been conducted regarding the implementation of murabahah financing at the Berkah Syariah Cooperative, West Bandung Regency with the management of the Berkah Syariah Cooperative, it can be concluded that the Berkah Syariah Cooperative has implemented murabahah financing in accordance with sharia principles and in accordance with the DSN MUI fatwa no. 04/DSN-MUI/IV/2000.